PENGARUH SIKLUS KONVERSI KAS TERHADAP LIKUIDITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - B11110015, Siti Hutami (Jurnal Manajemen Update, 2015)
This research aims at examining  the effect of cash conversion cycle on liquidity of basic and chemistry industry which are listed on Indonesia Stock Exchange in the period 2010-2013. There are two control variables that are used in this research, such as firm size and financial leverage. This research is a  quantitative research utiliting a sample of 25 company selected by using purposive sampling technique. Data is then analized by using multiple regression analysis. The results of the analysis show that cash conversion cycle and firm size  has a positive significant effect on liquidity, while financial leverage has a negative significant effect on liquidity. Based on this research,  the management of company  should manage the cash management effectively and efficiently in order that the company can resolve their short-term liabilities. Keywords: Cash Conversion Cycle, Firm Size, Financial Leverage, and Liquidity.